2013
DOI: 10.1128/jcm.01262-13
|View full text |Cite
|
Sign up to set email alerts
|

Adult Invasive and Noninvasive Infections Due to Streptococcus dysgalactiae subsp. equisimilis in France from 2006 to 2010

Abstract: We characterized 182 Streptococcus dysgalactiae subsp. equisimilis isolates and analyzed the epidemiological data on the corresponding infections. stG6, stG485, and stG6792 were the 3 most prevalent invasive emm types among the 27 different emm types recovered. High rates of antimicrobial resistance were observed for macrolides (26.4%) and tetracycline (34.6%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 33 publications
1
36
2
Order By: Relevance
“…Very few studies have been conducted on nGCGS, and to our knowledge, the finding has not previously been reported [17,27]. It is unclear, though, if this represents a true decrease in nGCGS morbidity.…”
Section: Discussioncontrasting
confidence: 63%
“…Very few studies have been conducted on nGCGS, and to our knowledge, the finding has not previously been reported [17,27]. It is unclear, though, if this represents a true decrease in nGCGS morbidity.…”
Section: Discussioncontrasting
confidence: 63%
“…The overall resistance rate to erythromycin in our study was similar to that reported in south India (12.2 %) for group C and G streptococci from humans (Prabu & Menon, 2013). However, a higher level of macrolide resistance (26.4 %) was detected for SDSE in France from 2006 to 2010 (Loubinoux et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Both group C and group G streptococci cause sporadic and epidemic pharyngitis that is clinically indistinguishable from GAS in school age children and in adults (13)(14)(15)(16). Early treatment may reduce the duration of symptoms, limit spread to susceptible contacts, and prevent invasive infections (17,18). A. haemolyticum causes pharyngitis primarily in adolescents and young adults presenting with clinical features that overlap those of GAS pharyngitis (11,19,20).…”
Section: Counterpointmentioning
confidence: 99%
“…Recently, we have shown that patients can collect their own throat swabs (and parents can collect their child's throat swab), yielding PCR results equivalent to those from health care workercollected swabs (18). As a result, we have incorporated the option of patient self-swabbing (or parental swabbing of children) into our process.…”
mentioning
confidence: 99%